STRATEGI ADAPTASI MASYARAKAT PASCA PEMBANGUNAN EKOWISATA DI DESA SENDI, KABUPATEN MOJOKERTO - INDRAYANINGTIAS, RISTANTI (Paradigma, 2021)
Development is something that will happen to social life, the existence of development will bring about changes in the impact of society. Ecotourism development in Sendi village brings various changes that cannot be avoided by the community. To cope with these changes, residents must be able to adapt in certain ways or actions. The village community in Sendi is a village community that is far from modern, for this reason, the existence of ecotourism is a challenge for residents to maintain their survival. The existing challenges must be able to be overcome by all residents, if the residents cannot overcome the challenges that are in front of them after the ecotourism is built, new social problems will arise. Therefore, the formulation in this study is how the adaptation strategy carried out by the community after the ecotourism development in Sendi village. The method used in this study is qualitative methods, the use of qualitative methods aims to provide a clear picture of the strategies that have been carried out by the people of Sendi. The results showed that the methods used by the community were building interaction with visitors, building cooperative relationships among villagers, building trust, holding existing values ??and norms, and building networks for the development of ecotourism in their villages. Keywords : Adaptation Strategy, Ecotourism, Society